Estimation of the postmortem interval by non-linear programming in conditions of changing ambient temperature - G. V. Nedugov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
The aim of the study is to evaluate the possibilities of determining the postmortem interval by non-linear programming in conditions of changing ambient temperature. A computer simulation of the cooling of the core of a corpse under conditions of linearly varying ambient temperature was performed and the possibilities of determining the postmortem interval with changes in the ambient temperature regime by non-linear programming were analyzed. It has been established that non-linear programming can be successfully used to determine the postmortem interval in conditions of changing ambient temperature. To do this, the computational algorithm of the method should take into account the ambient temperature recorded during the primary thermometry of the corpse at the place of its discovery as a constant. The obtained approximation estimates, depending on the increasing or decreasing nature of the ambient temperature, represent, respectively, the maximum or minimum limit value of the postmortem interval. The magnitude of the bias of the approximation estimate and the actual time of death can be calculated using the developed regression equations, the implementation of which requires a preliminary determination of the value of the average ambient temperature for the postmortem period estimated by non-linear programming. The proposed adaptation of the non-linear programming method is recommended for expert determination of the postmortem interval in conditions of changing ambient temperature.